2021
DOI: 10.1007/s00068-021-01647-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the stress response to improve outcomes for older patients undergoing emergency surgery with the addition of beta-adrenergic blockade

Abstract: As population age, healthcare systems and providers are likely to experience a substantial increase in the proportion of elderly patients requiring emergency surgery. Emergency surgery, compared with planned surgery, is strongly associated with increased risks of adverse postoperative outcomes due to the short time available for diagnosis, optimization, and intervention in patients presenting with physiological derangement. These patient populations, who are often frail and burdened with a variety of co-morbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 150 publications
(174 reference statements)
0
21
0
1
Order By: Relevance
“…The OFS could accordingly be useful for identifying these high-risk patients early on, which could aid in a more effective allocation of expertise and resources, such as multidisciplinary interventions. 15 It could also be a useful tool for communicating with patients and their relatives. Frailty as a concept can be challenging for patients to understand, which is understandable given that even clinicians at times struggle with the subject.…”
Section: Discussionmentioning
confidence: 99%
“…The OFS could accordingly be useful for identifying these high-risk patients early on, which could aid in a more effective allocation of expertise and resources, such as multidisciplinary interventions. 15 It could also be a useful tool for communicating with patients and their relatives. Frailty as a concept can be challenging for patients to understand, which is understandable given that even clinicians at times struggle with the subject.…”
Section: Discussionmentioning
confidence: 99%
“… 1–6 31 34–38 These comorbidities, along with the acute injury, have a negative impact on the cardiovascular system as well as other organ systems, which may affect the postoperative risk of adverse events. 7–9 14 Furthermore, studies have shown that several other factors could increase the risk of postoperative adverse events after hip fracture surgery, such as surgical duration, out-of-hours surgery, and dementia. 5 19–22 24 25 31 However, these variables have not been taken into account in the previous studies on this topic.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Hip fracture patients are often frail and suffer several insults in a short period: the insult from the trauma causing the fracture, the insults from fasting and preparing for surgery, the insult from anesthesia, as well as the insult from the hip fracture surgery. 7–9 14 Recently, Neuman et al published a prospective randomised trial where 1600 patients were included in the New England Journal of Medicine . They investigated the effects of spinal anesthesia compared with general anesthesia on the functional outcome and demonstrated no differences in the relative risk (RR) of recovered ambulation (RR (95% CI): 1.06 (0.82 to 1.36)), delirium (RR (95% CI): 1.04 (0.84 to 1.30)), or survival (RR (95% CI): 0.97 (0.59 to 1.57)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These TBI patients should reasonably be expected to require a different management strategy compared to their healthier counterparts. Using the RCRI, these high risk patients may be identified early on which could allow for a more efficient allocation of expertise and resources [46]. It could also enable the quantification of risk for patients and family members to aid them in participating in the decision making process around critical care, operative interventions, and even goals-of-care [47,48].…”
Section: Discussionmentioning
confidence: 99%